An Assessment of the Environmental Impacts of Catchment Management on the Status of Pong Wetland in District Kangra of Himachal Pradesh - Loria, Nancy; Verma, K. S.; Bhardwaj, S. K. (International Journal of Bio-resource and Stress Management, 2023)
The study on the environmental impacts of catchment management on the status of Pong wetland was conducted during the year 2011-12 in the immediate catchment of Pong reservoir. Four main tributaries viz., Buhal, Dehar, Gaj and Banerwere selected to determine spatial trends in nutrient concentrations and to relate these trends to different land use systems in the catchment. Each tributary was divided into four sites of 5 km each. Site which does not form the catchment of Pong reservoir was excluded. Nutrient concentrations at most of the sites within the catchment were found within the permissible limits. However, no spatial trend was observed along a longitudinal gradient in the nutrient concentrations of tributaries taken under study. Spatial distribution of land use system in the catchment of wetland corroborated that catchment under study covered maximum area under forest land use followed by cultivated land and barren land. Three representative samples of silt at different locations were collected from the lake at the point of their entry into the lake and were used to analyze for certain heavy metals like Cd, Fe, Cu, Zn. Silt characteristics of lake were showed that lake sediments contain heavy metals but ranged within the permissible limits. However, increase in their concentration in near future may cause changes in the physico-chemical composition of the lake water. Improved management and maintenance of catchment land use systems are crucial and there is a need to conserve and preserve these existing wetlands to maintain and improve the ecological balance